Hakikat Media Pembelajaran Menulis di Kelas Tinggi - Fadhilah Hilmy Nasution; Pramudia Ananda; Siti Fadilla; Juni Sahla Nasution (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
In learning Indonesian Language and Literature in elementary schools, especially in learning writing, the use of appropriate media is used because the lecture and assignment method alone is not effective but must be assisted with tools in the form of media. The choice of learning media must be adjusted to the child's level of development and learning objectives. In education, media can be interpreted as a tool that can be used as a channel for teacher messages in achieving teaching goals. Therefore, teaching media are better known as teaching aids or teaching aids. In this research, we conducted an effectiveness analysis regarding the nature of writing learning media in higher classes using the library study method. The results of the research show that the use of media in learning to write in higher classes is very necessary so that learning becomes effective and active, making it easier for students to facilitate learning.